Experiences of postmenopausal Iranian women living with urinary incontinence using hermeneutic phenomenology - Pakgohar, Minoo (2013)
The aim of this study was to explore experiences of living with urinary incontinence (UI) among postmenopausal Iranian women. Specifically, this research focuses on (1) the meaning of living with UI, (2) experiences of sexuality, and (3) experiences of seeking or not seeking treatment. Hermeneutic phenomenology underpinned the studies interpretive research approach. In-depth and semi-structured interviews were conducted in two sessions with 17 postmenopausal women aged between 52 to 68 years old. Interviews were conducted in participant‟s home and lasted 60-90 minutes per session. Verbatim transcriptions from audio-taped interviews were translated from Persian to English and formatted for data analysis. Emerging themes identified as the meaning of UI were disruption of normal functioning,self-imposed restrictions, and feelings of despair. „Disruption of normal functioning” signifies how UI intruded the women‟s personal life space; namely, emotional, spiritual, physical, and daily tasks. Self-imposed restrictions means that the women had to suppress their pleasures and needs as well as avoiding social relationship. Feelings of despair symbolizes adverse experiences that women had related to uncertainty about future, dependency, loneliness, hopelessness, and desire for death. Two dominant themes emerged in relations to experiencing sexuality: dependent upon husbands reaction to UI and redefining sexuality as intimacy. These themes indicate that womens experiences of sexuality were dependent upon husbands reaction and intimacy was more important than sexual intercourse. Experiences of for not seeking treatment were depicted by three themes including: developing daily management strategies, developing self perspective on urinary incontinence and establishing patient-doctor relationship. Two themes for experiences of seeking treatment were apparent: overcoming the barriers and anticipation of the future. Participants did not seek treatment due to taboos surrounding UI which lead them either to self manage or neglect UI. In addition, health care professionals were not open to discussing the subject. However, if participants could overcome the barriers,perceive potential risk of UI, and had high expectations of treatment then treatment seeking would follow. The findings reflect the need to educate the women on UI and to seek help as this condition can be treated. Health care providers need to be aware of the manifestations of UI among this vulnerable population for early diagnosis and improving their quality of life.